COMBINED MODEL OF HANQAVAN ORE FIELD (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The article deals with combined geological-structural, geophysical, oregeochemical graphic model of Hanqavan ore field. Due to the developed model, it is possible to determine the position of different types of mineralization within the gravity anomalies of the ore field and make some conclusions about its prospects. Once again, the presented model proves, that porphyry copper mineralization is characterized by maximum negative values of the local gravitational field.
Keywords: model; geological structure; geophysical anomaly; mineralization; ore field